Peran Manajemen Kepala Tata Usaha Dalam Meningkatkan Kualitas Pelayanan Administrasi Di Mts Al-Washiliyah Tembung - Annisa, Anti; Darmansah, Tengku (Media Manajemen Pendidikan, 2025)
This study aims to analyze the role of the head of administration in improving the quality of administrative services at MTs Al-Washliyah Tembung. Effective and efficient administrative services are essential in supporting the smooth running of the education process in madrasahs. In this context, the head of administration has a strategic responsibility as an administrative manager, starting from planning, organizing, to monitoring and evaluating services. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the head of administration plays an important role in improving the performance of administrative staff, optimizing the use of information technology, and creating a more structured and responsive work system. Obstacles such as limited human resources and facilities are still challenges, but can be overcome through training, good coordination between staff, and innovation in the service system. In conclusion, the managerial role of the head of administration is crucial in creating quality administrative services and supporting the achievement of madrasah education goals.